Transient Analysis of a Multi-phase Induction Machine Operating as Generator - Alok Kumar Mohanty; K B Yadav (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Multi-phase machines are considered serious contenders as compared to the three phase machines for variable applications in generating mode. This paper presents the transient performance analysis of a multi-phase induction machine operating in six-phase mode for power generation. In this paper the simulation and experimental analysis of a six-phase machine in generating mode have been made. The simulations are made and the machine functionality was investigated during no-load and when subjected to different types of loads. Experimental results are provided to confirm the ability of these models to represent during no load as well as during load period and the result were found to be satisfactory for power generation.